2009
DOI: 10.1086/599040
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid, Rifampin, Ethambutol, and Pyrazinamide Pharmacokinetics and Treatment Outcomes among a Predominantly HIV‐Infected Cohort of Adults with Tuberculosis from Botswana

Abstract: Background We explored the association between anti-tuberculosis drug pharmacokinetics and treatment outcomes among pulmonary tuberculosis (TB) patients in Botswana. Methods Consenting TB outpatients had blood collected 1, 2, and 6 hours after simultaneous isoniazid, rifampin, ethambutol, and pyrazinamide ingestion. Maximum serum concentrations (Cmax) and areas under the serum concentration-time curve (AUC0-6 h) were determined. Clinical status was monitored throughout treatment. Results Of 225 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
192
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(211 citation statements)
references
References 20 publications
14
192
3
2
Order By: Relevance
“…Bhatt et al 9 found that antiretroviral drugs did not influence exposure to RIF or INH when concomittantly administered in HIV-infected TB patients. Other studies, however, have found that HIV-infected TB patients receiving ART often have a lower exposure to RIF and INH 10 , 11 compared to HIV-negative individuals.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Bhatt et al 9 found that antiretroviral drugs did not influence exposure to RIF or INH when concomittantly administered in HIV-infected TB patients. Other studies, however, have found that HIV-infected TB patients receiving ART often have a lower exposure to RIF and INH 10 , 11 compared to HIV-negative individuals.…”
Section: Discussionmentioning
confidence: 92%
“…A debate also exists on the interaction between anti-retroviral drugs and Rifampicin in particular with the literature providing mixed messages on whether anti-retroviral therapy decreases Rifampicin exposure or doesn't affect it at all 9 , 10,11 .…”
Section: Tuberculosis (Tb) Is the Most Common Opportunistic Infectionmentioning
confidence: 99%
“…Doses of RIF, INH, pyrazinamide (PZA), and ETH were selected based on mean peak drug concentrations (Cmax) achieved in patients' serum (36)(37)(38). For these studies, Mtb was starved in PBS for 4 wk, then exposed to the four drugs simultaneously for 5 d, with two different doses of RIF-one based on Cmax data (3 μg/mL), and one already shown to create DD Mtb (10 μM; 8.2 μg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…[4,6] PK variability is a well-known problem affecting drug exposure and thereby TB treatment. [7,8] For example, Pranger et al observed a nine-fold variability in the area under the time concentration curve between 0 and 24 h (area under the curve [AUC 0-24 h ]) of moxifloxacin, possibly due to variation in protein binding.…”
Section: Pkmentioning
confidence: 99%
“…[7] Furthermore, Chideya et al found that pyrazinamide plasma concentrations below 35 µg/ml were a predictor of poor treatment outcome, which can function as a reference value in TDM. [6] However, more studies are needed to elucidate PK/PD indices in 'real life' treatment, because the PK/PD index (Table 1) of a drug in a combination regimen may differ from the index of that particular drug given as monotherapy in an EBA study.…”
Section: Efficacymentioning
confidence: 99%